PENGARUH MOTIVASI BELAJAR TERHADAP HASIL BELAJAR PEMASANGAN RITSLETING JEPANG PADA BAHAN BERFURING DI KELAS XI BUSANA 1 SMK NEGERI 8 SURABAYA - Aurilia, Bhernica Windy; Nashikhah, Ma’rifatun (Jurnal Socia Akademika, 2023)
This research aims to: 1) Find out the picture of students' learning motivation in learning how to install Japanese zippers installation on lined materials, 2) Find out the learning outcomes of students in learning how to install Japanese zippers on materials, 3) Find out whether or not there is an influence of learning motivation on learning outcomes in students. learning to install Japanese zippers on lined materials. The research method used is a descriptive quantitative method in the form of ex post facto. The subjects in this research were 34 respondents from class XI Busana 1 SMK Negeri 8 Surabaya. Data collection uses documentation and questionnaires. Data analysis uses descriptive statistics. The research results show that the test results are constant at 0.819, from the output the coefficient of determination (R Square) is 0.671, which means that the influence of the independent variable on the dependent variable is 67.1%. Based on the results of these data, it can be interpreted that 67.1% of learning motivation variables influence student learning outcomes. Meanwhile, the remaining 32.9% is explained by other factors not included in the model